Demonstration of a consensus approach for the calculation of physicochemical properties required for environmental fate assessments. (March 2018) - Tebes-Stevens, Caroline; Patel, Jay M.; Koopmans, Michaela; Olmstead, John; Hilal, Said H.; Pope, Nick; Weber, Eric J.; Wolfe, Kurt
Abstract: Eight software applications are compared for their performance in estimating the octanol-water partition coefficient (Kow ), melting point, vapor pressure and water solubility for a dataset of polychlorinated biphenyls, polybrominated diphenyl ethers, polychlorinated dibenzodioxins, and polycyclic aromatic hydrocarbons. The predicted property values are compared against a curated dataset of measured property values compiled from the scientific literature with careful consideration given to the analytical methods used for property measurements of these hydrophobic chemicals. The variability in the predicted values from different calculators generally increases for higher values of Kow and melting point and for lower values of water solubility and vapor pressure. For each property, no individual calculator outperforms the others for all four of the chemical classes included in the analysis. Because calculator performance varies based on chemical class and property value, the geometric mean and the median of the calculated values from multiple calculators that use different estimation algorithms are recommended as more reliable estimates of the property value than the value from any single calculator. Highlights: Eight software applications for physicochemical property estimation are compared. Measured property values of PCBs, PBDEs, PCDDs and PAHs compiled to assess performance. Property compilation includes Kow, melting point, vapor pressure and water solubility. Robust consensus values are obtained from geometric mean or median of the predictions.